Effects of sexism in the workplace on mental health: a systematic review - Simionato, Natalia Maria (2020)
Objective: To identify the effects of sexism in the workplace (in the forms of sexual harassment, payment inequality, career progression obstacles and sex discrimination) on workers’ mental health through a systematic review of the scientific literature. Method: A search strategy with Boolean Operators, MeSH terms and keywords related to working women, sexual and workplace harassment, gender pay gap, career mobility and depressive symptoms or disorders was applied in five databases (PubMed, PsycInfo, Web Of Science, LILACS and CINAHL), from which 1613 articles were analysed by title and abstract, 314 read in full by two reviewers and 105 matched the inclusion criteria. Data of interest from 58 articles were not available for extraction, thus these were excluded. Comorbidities (e.g., anxiety, post-traumatic stress disorder, sleep problems) were only included if the study also assessed depression. The final sample consisted of 47 articles, which had their methodology assessed though the Newcastle-Ottawa Scale. Results: The most commonly studied subject was sexual harassment. Several work areas and different country populations are represented in these articles, being the Unites States of America the most common affiliation source of authors. All studies were published by, or in collaboration with Universities in developed countries. Few studies considered gender according to self-report and the intersection between sex and race, highlighting the need for more studies about sexism in the workplace being conducted around the world, especially in underdeveloped and developing countries, which are currently underrepresented. Data extracted from 47 articles suggest that women are more exposed to sexual harassment and assault in the workplace, have lower salaries, face more gender-related barriers to job promotions and are more exposed to sex discrimination at work. These exposures seem to increase the risk for depression and comorbidities regardless of sex, although women are, in general, more exposed and more affected by these disorders. Conclusion: Women are, in general, more exposed to all sexism-related events at work. Exposure to sexual harassment or assault in the workplace, gender wage gap, difficulties in job promotions or career progression and sex discrimination at work seem to promote mental health disorders such as depression and comorbidities in both sexes. Some results suggest that men might be more vulnerable to develop psychological disorders after being sexually harassed or assaulted in the workplace, however, women are more exposed and more affected by the disorders evaluated in this review.